Changing Paradigms of Engineering Education - An Indian Perspective - Madheswari, S. Pavai; Mageswari, S.D. Uma (Procedia computer science, 2020)
VUCA (Volatile, uncertain, complex and ambiguous) characterize the engineering education scenario. Engineers form the backbone of any country’s economy. Around 25% of the world’s engineers are in India but it lags behind in research and innovation. At the global level, engineering education is experiencing a paradigm shift from teacher-centric to student-centric teaching- learning process, content based education to outcome based education, knowledge seeking to knowledge sharing classrooms, teachers to facilitators, traditional engineering disciplines to interdisciplinary courses, chalk and board (lecture based) learning to technology driven learning and the list goes on. But in India, still conventional teaching – learning practices with little practical training is adopted in many institutions. This is shown by the fact the Indian institutions still struggle to make a position in world ranking with few exceptions. A country which pioneered in engineering, medicine, arts and music etc. in ancient era, suffers major setbacks in technical education. Hence this study attempts to analyse the perception of stakeholders, viz. students, parents, academic faculty and industry, on engineering education and the future of engineering education. Focus group consultations with select group of respondents were carried out. The results were analysed which showed that the students perceive positively on engineering education but at the same time are apprehensive about the position of engineers in the society. Parents’ perception towards engineering is solely on the job opportunities but the faculty members opined changes in the mindset of students and the impact of social media on general attitude. Industries expressed lack of employable engineers and lack of skills in new age technologies. Overall the respondents favoured the introduction of new and multidisciplinary courses to meet future demands.